Case Report: Gutter endoleak embolization in a patient with bilateral common iliac artery aneurysms treated with sandwich parallel grafts - Lee, Sangho; Kim, Hyeonju; Huh, Seung; Kim, Hyung-Kee (Frontiers in Surgery, 2024)
BackgroundCurrent guidelines recommend preserving at least one of the bilateral pelvic flows in patients with aortoiliac aneurysms. The sandwich parallel graft, using commercially available devices, provides a viable option for patients who fall outside the instructions for use of iliac branch devices. However, gutter endoleak remains a significant challenge.Case reportA 78-year-old woman with an incidentally discovered small AAA and bilateral CIAAs experienced aneurysmal growth to 42 mm for the abdominal aortic aneurysm (AAA) and 41 mm and 33 mm for the right and left common iliac artery aneurysms (CIAAs), respectively. Morphologic assessment of the aortoiliac aneurysm revealed the nearly 90-degree angles of the bilateral iliac bifurcations and the tortuous path of the internal iliac arteries. The iliac branch device was considered relatively contraindicated and ineligible; therefore, to preserve pelvic blood flow, the decision was made to employ the sandwich parallel graft technique in the left iliac arteries. Following the placement of the sandwich graft within the iliac limb, standard procedures were carried out. However, completion angiography revealed a type IA endoleak and a significant gutter endoleak in the left CIAA extending to the AAA sac. Despite the extension of overlapping zone, the gutter endoleak persisted after a 10 min waiting period. Therefore, we then advanced an 014 wire and a microcatheter to selectively access the gutter endoleak and performed embolization using multiple detachable coils. The final angiography showed complete resolution of the gutter endoleak and computed tomography angiography 1-month postoperatively confirmed the absence of any endoleaks.ConclusionThis case report highlights that targeted embolization is a feasible and effective treatment for significant gutter endoleak following the sandwich parallel graft technique.